The Impact of Leadership Style and Work Environment on Employee Performance at PT ISS Indonesia, Denso Area, Cikarang - Anindya, Alya; Octaviani, Irma Sari (Pascasarjana Universitas Pasundan, 2025)
This study aims to analyze the influence of leadership style and work environment on employee performance at PT ISS Indonesia Area Denso Cikarang. The study used a quantitative method with a descriptive and causal approach. The population of this study was all employees of the company, with a sample of 71 respondents selected using the Slovin method. Primary data were obtained through questionnaires filled out by respondents. Data analysis used simple and multiple linear regression tests. The results showed that leadership style had a partial significant effect on employee performance (tcount> ttable; 1.734> 1.667; sig. 0.087 <0.05). The work environment also had a partial significant effect on employee performance (tcount> ttable; 2.339> 1.667; sig. 0.022 <0.05). Simultaneously, leadership style and work environment had a significant effect on employee performance (Fcount> Ftable; 19.084> 3.132; sig. 0.000 <0.05).